Volume 4: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27908
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement by Impingement Cooling in a Combustor Liner Heat Shield

Abstract: As part of an industrial gas turbine research program, the present study provides the results of a basic investigation of the heat transfer in an impingement cooled combustor heat shield. Because of the complexity and the irregularity of the impingement pattern of the heat shield, standard correlations for regular impingement fields are insufficient and the investigation of local heat transfer enhancement is required therefore. The model to represent a simplified heat shield is made out of perspex, and heat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, it was possible to avoid uncertainties due to comparing results from different experiments. More details on the equipment used for the TLC measurements are given in [11] and [12]. The evaluation of the TLC data was done with the program ProTeIn developed at the Institute of Aerospace Thermodynamics (ITLR).…”
Section: Measurement Methods and Equipmentmentioning
confidence: 99%
“…Thus, it was possible to avoid uncertainties due to comparing results from different experiments. More details on the equipment used for the TLC measurements are given in [11] and [12]. The evaluation of the TLC data was done with the program ProTeIn developed at the Institute of Aerospace Thermodynamics (ITLR).…”
Section: Measurement Methods and Equipmentmentioning
confidence: 99%
“…Esposito et al [5] performed related studies for the influence of corrugated walls and extended port geometries on the heat transfer of impingement cooling. Lauffer et al [6] investigated different impingement cooling schemes and showed an increase of the Nusselt number locally and spatially with an increasing jet Reynolds number.…”
Section: Related Past Investigationsmentioning
confidence: 99%
“…In electronics and power electronics devices [1], personal computer central processing units [2], blades and casings of gas turbines [3][4][5][6][7][8][9][10], combustion chamber liners of gas turbine engines [11,12], and magnetically confined plasma fusion reactors [13,14] macroscale and microscale multi-jet impingement and impingement-effusion high-heat flux cooling systems are utilized. To enhance heat transfer, a very high, nearly uniform heat transfer coefficient (HTC) distribution can be obtained at the stagnation zones of immersed jets injected from multiple orifices or nozzles having a one-dimensional (1D) or two-dimensional (2D) configuration, located over a smooth or roughened impingement surface.…”
Section: Introductionmentioning
confidence: 99%